Association of exposure to a mixture of phenols, parabens, and phthalates with altered serum thyroid hormone levels and the roles of iodine status and thyroid autoantibody status: A study among American adults - Qian Gao; Yu Song; Zexin Jia; Changsheng Huan; Qingqing Cao; Chongjian Wang; Zhenxing Mao; Wenqian Huo (Ecotoxicology and Environmental Safety, 2024)
Background: Toxicological and epidemiological studies have shown that environmental endocrine disruptors interfere with hormonal homeostasis. However, there is limited research on the effects of mixed exposure to nonpersistent endocrine disruptors on thyroid hormones and the factors (e.g., presence status of thyroid autoantibodies or nutritional status of organismal iodine) that may influence this association. Methods: Data were collected from the National Health and Nutrition Examination Survey (NHANES) 2007–2008 and 2011–2012. Relationships between single pollutants and thyroid hormone and thyroid autoantibody levels were assessed using generalized linear (GLM) and restricted cubic spline (RCS) regression models. Weighted quantile sum regression (WQS), group-weighted quantile sum regression (GWQS), quantile-based g-computation (qgcomp), and adaptive elasticity network (AENET) were applied to assess the mixed exposure effect. Next, subgroup analyses were performed on the basis of the urinary iodine concentration or thyroid autoantibody status to assess the modifying role of urinary iodine and thyroid autoantibodies. Results: A total of 2385 study participants were included in this study. Both the single-pollutant model and the multipollutant mixed model revealed that parabens and bis(2-ethylhexyl) phthalate (DEHP) metabolites were significantly and negatively associated with serum thyroxine (T4) levels. However, no associations were found between the target pollutants and thyroid autoantibodies (thyroglobulin antibodies (TgAb) and thyroid peroxidase antibodies (TPOAb)). In addition, this study revealed that urinary iodine or thyroid autoantibody status altered the associations of some of the target pollutants with thyroid hormones. WQS and qgcomp analyses, revealed that the associations of mixed pollutants with hormones differed depending on the urinary iodine or antibody status, especially T4 and thyroid-stimulating hormone (TSH). Conclusion: Significant associations were found between phenols, parabens, and phthalates and serum thyroid hormone levels, with parabens and DEHP metabolites playing major roles. Urinary iodine and thyroid autoantibody status act as modifiers between environmental endocrine-disrupting pollutants and thyroid hormones.